Regency Analysis of the Problem of Low Literacy Skills of Elementary School Students in Dompu - Khairul Khalqi; Sri Haryanti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the problems and low literacy skills of students, especially at the elementary school of Madrasah Ibtidaiyah (MI) Al-Faat Bara. This study uses a descriptive analysis method based on qualitative data through observations and interviews conducted at the elementary school of MI Al-Faat Bara. While the research subjects are elementary school students / MI. As well as the parents of the students. Based on the results of the study, it shows that the factors causing the low literacy skills of MI Al-Faat Bara students are: 1. Low interest in reading; 2. Insufficient facilities and infrastructure; 3. Relationships in the family; 4. The influence of cellphones and television; 5. Teachers have not maximized the model in learning to read.